Modification of Peatlands Amendment with Dolomite and Fly Ash - Zulkarnaini Zulkarnaini; Irfan Suliansyah; Gusmini Gusmini; Syafrimen Yasin (UNIVERSITY OF LAMPUNG, 2026)
High acidity levels and low availability of alkaline elements such as Ca, Mg, and K inhibit plant growth and reduce land productivity. This study examined the effect of dolomite and fly ash doses on the chemical properties of peatland. This study used a 2 × 3 factorial randomized block design (RBD) with three replicates. The first factor was the type of soil conditioner, namely dolomite and fly ash. The second factor was the soil conditioner dose, namely 5, 10, and 15 t ha-1. The type of soil ameliorant did not interact significantly with the dose of soil conditioner for pH, water content, organic C, total N, K, P, Fe, Cu, Zn, Mg, Ca, K-exch, and humate. Dolomite was superior in increasing base elements (Ca, Mg, and K) and the humification process of organic matter, while fly ash played an important role in increasing microelements (Fe, Cu, Zn) and carbon stabilization. Meanwhile, an ameliorant dose of 15 t ha-1 significantly increases pH, moisture content, organic carbon, and macronutrients (P and K). Dolomite and fly ash at an optimal dose of 15 t ha-1 are recommended as a sustainable amelioration strategy to increase pH, chemical fertility, and carbon stability in peat soils without causing negative environmental impacts.